Aesthetics of composition in drawing Shife Hadi (Journal of the College of Basic Education, 2022)
This research is concerned with studying (aesthetics of training in drawing a Hadi healing )through four chapters . The first chapter includes the research problem with the following questions : Does the real, subjective, and technical data have a prominent effect on the manifestation of the aesthetics of the formation in the drawing of a quiet healing? And Is it possible to tag aesthetic concepts behind the work of the components of the formation and its reasons represented by its harmonious constructive patterns? Did Hadi's healing experience lead to an aesthetic in training that gave him a specificity that warrants research? The importance of the research was evident in being a transformer to shed light on the aesthetic values based on structural elements that combine drawing and composition, as well as in how to show the value of structural constructions in escalating the aesthetic form of the painting by reading the formative surface on constructive foundations. The actress,( Shife Hadi), is one of the Iraqi artists who contributed to supplementing the plastic movement with creative works, and this research contributes to supplementing the plastic cultural reality with a new addition. The research has one goal: to know the aesthetics of training in Hadi's healing drawing. The boundaries of the research were limited to studying the composition in oil paintings and karlik made in Iraq, and the terms were defined to serve the subject of the research. As for the second chapter (the theoretical framework), it included three sections, the first topic dealt with (the aesthetics of training in Iraqi painting) and the second topic (employing the popular heritage in contemporary Iraqi painting) and the third topic (the experience of the actress Shife Hadi). As for the third chapter, the research procedures were completed and it included the research community consisting of (15) models, and (4) models were intentionally chosen to achieve the goal of the research, while the researcher took a descriptive and analytical approach in analyzing the sample models. The fourth chapter contains the findings and conclusions reached by the researcher:1 - The use of different techniques in one painting achieved aesthetic, semantic and expressive dimensions on the general composition of the painting.2- Adopting the color harmony in most of the paintings as an aesthetic value 3- Expressive realism was the hallmark of the actress, Shife Hadi's work 4- It was characterized by a renewed vision and transformations according to the shapes and vocabulary systems of ancient Iraqi art, as symbols, heritage and local units.